Current Trends in Practice of Residents in the Saudi Board of Endodontics Program - AlRahabi, Mothanna K.; AlKady, Ayman M. (European Journal of Dentistry, 2019)
Objectives The purpose of the current study was to collect information about some techniques and armamentarium currently used by the Saudi Board of Endodontics residents in relation to the technical steps of root canal therapy.Materials and Methods A web-based survey was sent to the Saudi Board of Endodontics residents, based in the western area of Saudi Arabia. The survey assessed controversial concepts, and collected information regarding new instruments and materials, used in the technical steps of nonsurgical root canal treatment. A one-sample chi-square test, with a 95% level of significance, was applied to determine whether there were significant differences between respondents’ answers.Results A total of 45 out of 50 residents (90%) responded to the questionnaire. The majority of Saudi Board residents of Endodontics, who participated in this survey, used the mean of working length (ML) measured by periapical X-Ray and apex locator in the presence of a radiographic lesion (63.3%), and maintained apical patency in all cases (80.0%). ProTaper Universal (40%) and ProTaper Next (41.2%) were the most common NiTi rotary systems used for root canal instrumentation. Thirty percent of respondents used adjunct device with irrigation, and 80% advocated smear layer removal. Zinc oxide–eugenol-based sealers were the most common used sealers (70%), and most residents (86.6%) did not advocate sealer extrusion.Conclusions This study revealed that residents of the Saudi Board of Endodontics program adopt new endodontic technologies. There is, however, a need for more investigations regarding this objective, including responses from all residents in Saudi Arabia.
Keywords: Saudi Board of Endodontics; endodontic therapy; radiography; root canal; surveys; technology